Two‐Dimensional Mesoscale‐Ordered Conducting Polymers. (7th September 2016) - Liu, Shaohua; Zhang, Jian; Dong, Renhao; Gordiichuk, Pavlo; Zhang, Tao; Zhuang, Xiaodong; Mai, Yiyong; Liu, Feng; Herrmann, Andreas; Feng, Xinliang
Abstract: Despite the availability of numerous two‐dimensional (2D) materials with structural ordering at the atomic or molecular level, direct construction of mesoscale‐ordered superstructures within a 2D monolayer remains an enormous challenge. Here, we report the synergic manipulation of two types of assemblies in different dimensions to achieve 2D conducting polymer nanosheets with structural ordering at the mesoscale. The supramolecular assemblies of amphipathic perfluorinated carboxylic acids and block co‐polymers serve as 2D interfaces and meso‐inducing moieties, respectively, which guide the polymerization of aniline into 2D, free‐standing mesoporous conducting polymer nanosheets. Grazing‐incidence small‐angle X‐ray scattering combined with various microscopy demonstrates that the resulting mesoscale‐ordered nanosheets have hexagonal lattice with d‐spacing of about 30 nm, customizable pore sizes of 7–18 nm and thicknesses of 13–45 nm, and high surface area. Such template‐directed assembly produces polyaniline nanosheets with enhanced π–π stacking interactions, thereby resulting in anisotropic and record‐high electrical conductivity of approximately 41 S cm −1 for the pristine polyaniline nanosheet based film and approximately 188 S cm −1 for the hydrochloric acid‐doped counterpart. Our moldable approach creates a new family of mesoscale‐ordered structures as well as opens avenues to the programmed assembly of multifunctional materials.